STANDARDISASI PROSES DALAM UPAYA PENINGKATAN PRODUKTIFITAS DI PROSES MULTI VARIASI - Yahdi Firmansyah (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
The improvement of productivity is a wise way to fulfill market demand at this competitive era. However, still found facts on field a problem in formulating it, especially to the process with variations. Un-standardized process can lead to ineffective productivity measuring. Wrong measurement could affects to wrong the decision making. This paper was aimed to present real correction to productivity formulation, also the combination of MUDA elimination in an improvement. 5S concept, also emphasized in this effort as other tools in Japanese improvement perspective, KAIZEN. The method used in this research was field study and their related references, including seminar. The result of this research is to describe what exact formulation and elimination of MUDA can be used as the tools to improve productivity at a production line. Through field and literature study, with correct formulation, the productivity of a production line can be effectively and clearly displayed. A Significant improvement can be shown clearly as well.